Las excepciones previas y su incidencia jurídica en las resoluciones dentro de los juicios de alimentos, emitidas por la Unidad Judicial Familia, Mujer, Niñez, y Adolescencia con sede en el cantón Riobamba, durante el período de mayo a diciembre del 2016. - Yánez Rodríguez, Rosario Luzmila (2017)
The previous exceptions appear with the General Organic Code of Processes in Art. 153, so they must be proposed by the defendant after it has been cited in legal and due form, when answering the demand and in a certain way are the unique that will make mention for your defense. The structure of the present research work is developed in the following way: the preliminary pages, the introduction, the approach of the problem, the justification, the general objective and the specific objectives, where we observe that the present investigative work is feasible, novel, original that serves for lawyers, students of law and citizenship in general. The state of the art related to the thematic or theoretical framework, where the instrument of the signing was applied, which was obtained through doctrines, theories, concepts and bibliographic articles extracted from codes, books, regulations, laws and texts, building the part Theoretical, conceptual, legal and doctrinal of the investigation, this is where the food judgment, the exceptions and the legal incidence of the previous exceptions within the food trials are found; the methodology where we find the types of research, the scientific method, the population and the sample, the techniques and instruments of data collection, applying the analytical method to perform a critical and legal method; the results and discussion; the conclusions and recommendations; the bibliography, annexes and the opinion by the members of the court.